Effect of quartz overgrowth precipitation on the multiscale porosity of sandstone: A (U)SANS and imaging analysis. (1st June 2015) - Anovitz, Lawrence M.; Cole, David R.; Jackson, Andrew J.; Rother, Gernot; Littrell, Kenneth C.; Allard, Lawrence F.; Pollington, Anthony D.; Wesolowski, David J
Abstract: We have performed a series of experiments to understand the effects of quartz overgrowths on nanometer to centimeter scale pore structures of sandstones. Blocks from two samples of St. Peter Sandstone with different initial porosities (5.8% and 18.3%) were reacted from 3 days to 7.5 months at 100 and 200 °C in aqueous solutions supersaturated with respect to quartz by reaction with amorphous silica. Porosity in the resultant samples was analyzed using small and ultrasmall angle neutron scattering and scanning electron microscope/backscattered electron (SEM/BSE)-based image-scale processing techniques. Significant changes were observed in the multiscale pore structures. By 3 days much of the overgrowth in the low-porosity sample dissolved away. The reason for this is uncertain, but the overgrowths can be clearly distinguished from the original core grains in the BSE images. At longer times the larger pores are observed to fill with plate-like precipitates. As with the unreacted sandstones, porosity is a step function of size. Grain boundaries are typically fractal, but no evidence of mass fractal or fuzzy interface behavior was observed suggesting a structural difference between chemical and clastic sediments. After the initial loss of the overgrowths, image scale porosity (>∼1 cm) decreases with time. Submicron porosity (typically ∼25% of the total) is relatively constant or slightly decreasing in absolute terms, but the percent change is significant. Fractal dimensions decrease at larger scales, and increase at smaller scales with increased precipitation.